Assessment of Service Quality of Select Hospitals in Bengaluru with Reference to Outpatient Services - Jayanthi, R. (Gyan Management Journal, 2018)
The service industry plays an increasingly important role in the economy of many countries. In today's global competitive environment delivering quality service is considered as an essential strategy for success and survival {Parasuramanet al., 1985; Reich held and Sasser, 1990; Zeithaml et a/., 1990).Health care managers are increasingly under pressure to have 'customer centric' practices that are directed towards providing best medical services to their clients for the hospital to be successful.The purpose of this paper is to measure service quality of select private hospitals with reference to outpatient services.This paper assesses patient's expectation and satisfaction pertaining to hospital service quality with special reference to OPD. Data collected from 192 patients of 10 hospitals are analyzed using SERVQUAL model. The model compares patients perception and expectation of services received across five dimensions of service quality like tangibility, responsiveness, assurance, reliability and empathy.The result of this study reveals that overall service quality score is positive; however there were service quality gaps in all the dimensions of the scale. The service quality level of the out patients in the hospitals is moderate, in addition the largest positive gap between patient's perception and expectation is in terms of tangibility and responsiveness the largest negative gap is empathy and assurance. The findings help the hospital management team to understand areas of improvement towards better health care.
Keywords: Hospitals; Service quality; SERVQUAL; Healthcare